PEMBINAAN KARAKTER PEDULI LINGKUNGAN MELALUI PROGRAM LISA (LIHAT SAMPAH AMBIL) DI SMPN 10 MATARA - Rahmi, Lalu Sumardi, Muh. Zubair (JURNAL PENDIDIKAN IPS, 2026)
The increasingly concerning waste problem requires solutions not only technically, but through behavioral changes and the development of environmentally conscious community characters. This study aims to describe the implementation, impacts, and supporting and inhibiting factors of the LISA Movement (See Trash Pick Up) in developing environmentally conscious characters at SMPN 10 Mataram. This study uses a qualitative approach with a case study type. Data were collected through semi-structured interviews, passive participant observation, and documentation. Data validity was tested by triangulation of sources, techniques, and time. Data analysis followed the Miles, Huberman, and Saldana model which includes data condensation, data presentation, and conclusions. The results of the study indicate that: (1) The implementation of the LISA Movement is structured through routine morning activities, breaks, and after school with a unique mechanism of "trash as a return ticket" which is the program's hallmark and involves all parties in the school; (2) The LISA Movement has a positive impact on the development of environmentally conscious characters as reflected in changes in student behavior, the formation of an environmentally conscious school culture, and improvements in the physical condition of the school environment; (3) Supporting factors include the commitment of the school community, the leadership of the principal, external support, the active role of the OSIS and the waste bank team, and adequate infrastructure, while the inhibiting factors are the diversity of student backgrounds, technical constraints on waste sorting, limited time for character development, and internal student factors such as laziness.